The Roman Virtue of Pietas and the Glorification of the Deceased Wife (CIL VI, 1527 “Laudatio Turiae”) - Alekna, Darius (Literatūra, 2020)
The subject of this paper is the multiplicity of meaning of the word pietas as it is used in the famous inscription CIL VI, 1527 called Laudatio Turiae. In revealing traditional and innovative aspects of this notion, the author tries to see the ideology of relations in the Roman family of the laudator and the laudata behind it, and to set it into the context of the changing world in the times of the Late Republic and the Principate within the Roman history. The inscription reveals that, in the eyes of laudator, pietas is the most important virtue of his defunct wife, laudata. In the course of the research, three features of pietas are marked out: 1) the virtue of pietas is operative exclusively in the sphere of family relations; 2) pietas relations always presuppose the hierarchical ones (e.g. children to the father / mother, wife to husband, younger brother / sister to the elder one); 3) the virtue of pietas always implies a strong action. Some new aspects of the functioning of the virtue of pietas can be observed when exploring the usage of the word in the inscription. For the first time in the Latin literature, the word pietas signifies the transfer of the virtue of pietas into the female domain, using it to describe the relation of the younger sister to the elder. But the most striking innovation is an inversion of the hierarchical order of children to the parents. For the first time, pietas means the duty of the parents to bring up their children in the best manner possible – an obligation which will find its place in the Roman law codes. The large usage of the notion of pietas and experimentation with its meaning, which finds parallels in the poetry of the Augustan age (Virgil, Ovid) signifies the susceptibility of the laudator to the ideas of the Augustan policies and his ideological stances. The article is preceded by a Lithuanian translation of the inscription with a short introduction.